2008
DOI: 10.1161/circresaha.108.178533
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and Atherosclerosis Induced by Chronic Intermittent Hypoxia Are Attenuated by Deficiency of Stearoyl Coenzyme A Desaturase

Abstract: Abstract-Obstructive sleep apnea leads to chronic intermittent hypoxia (CIH) and is associated with atherosclerosis. We have previously shown that C57BL/6J mice exposed to CIH and a high-cholesterol diet develop dyslipidemia, atherosclerosis of the aorta, and upregulation of a hepatic enzyme of lipoprotein secretion, stearoyl coenzyme A desaturase 1 (SCD-1). We hypothesized that (1) SCD-1 deficiency will prevent dyslipidemia and atherosclerosis during CIH; and (2) human OSA is associated with dyslipidemia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 58 publications
1
103
1
1
Order By: Relevance
“…OSA may promote generalized atherosclerosis through effects of intermittent hypoxemia, which activates the transcription factors hypoxia-inducible factor-1 and nuclear factor-kB, which, in turn, induce the expression of inflammatory cytokines and adhesion molecules implicated in atherosclerosis. Intermittent hypoxemia also has been shown in mice models to induce the hepatic enzyme, stearoyl coenzyme desaturase, leading to dyslipidemia and atherosclerotic lesions (24). The potential importance of OSA in increasing stroke risk through atherogenic pathways is consistent with the reported higher prevalence of internal carotid artery atherosclerotic lesions in stroke patients with compared with those without OSA (25).…”
Section: Discussionmentioning
confidence: 60%
“…OSA may promote generalized atherosclerosis through effects of intermittent hypoxemia, which activates the transcription factors hypoxia-inducible factor-1 and nuclear factor-kB, which, in turn, induce the expression of inflammatory cytokines and adhesion molecules implicated in atherosclerosis. Intermittent hypoxemia also has been shown in mice models to induce the hepatic enzyme, stearoyl coenzyme desaturase, leading to dyslipidemia and atherosclerotic lesions (24). The potential importance of OSA in increasing stroke risk through atherogenic pathways is consistent with the reported higher prevalence of internal carotid artery atherosclerotic lesions in stroke patients with compared with those without OSA (25).…”
Section: Discussionmentioning
confidence: 60%
“…Several studies reported such anomalies of lipid metabolism in both OSA-patients 8 and mice exposed to IH 7 , IH-related atherosclerosis appearing to be closely associated with lipid alterations 10,11,21 . However in our study, 14 days of IH in HCD-fed mice accelerated atherosclerosis development independently of total 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 cholesterol levels.…”
Section: Dyslipidemic Alterations Due To Ihmentioning
confidence: 99%
“…Most studies have not demonstrated significant differences in the prevalence of dyslipidemia between COPD patients and control subjects [56]. Chronic intermittent hypoxia has been shown to upregulate a hepatic enzyme of lipoprotein secretion, leading to elevated low-density lipoprotein cholesterol levels in patients with obstructive sleep apnea (OSA) [57]. This is a potential mechanism for some observations of higher cholesterol values in selected very severe COPD patients.…”
Section: Dyslipidemiamentioning
confidence: 99%